Exploring dyadic coping, self-efficacy, and quality of life in patients with cervical cancer and their spousal caregivers: an actor-partner interdependence mediated model analysis - Chuntao Wang; Yaling Wang; Longyan Bian; Fan Wu; Pornpat Hengudomsub; Chintana Wacharasin (BMC Nursing)
Abstract Background Cervical cancer and its treatment impose significant psychological and physical challenges for patients and their spousal caregivers. Understanding dyadic coping mechanisms and self-efficacy can significantly improve the quality of life (QoL) for both parties. However, research exploring these relationships from a dyadic perspective remains limited, particularly in the Chinese context. Methods This cross-sectional study involved 288 dyads of patients with cervical cancer and their spousal caregivers from five hospitals in Jiangsu Province, China, between November 2022 and August 2023. Participants completed validated scales, including the Dyadic Coping Inventory, the General Self-Efficacy Scale and the 12-item Short-Form health survey. The mediating role of self-efficacy in the relationship between dyadic coping and QoL was assessed using Actor-Partner Interdependence Mediation Model (APIMeM). Results Findings indicate significant actor and partner effects, suggesting that both patients’ and caregivers’ dyadic coping positively influences their own and each other’s self-efficacy and QoL. Mediation analyses revealed that: (1) patients’ and caregivers’ self-efficacy fully mediated the relationship between dyadic coping and mental QoL (MCS); while (2) patients’ self-efficacy partially mediated the relationship between dyadic coping and physical QoL (PCS). Spousal caregivers reported higher dyadic coping and self-efficacy scores, which were associated with better mental QoL (MCS) outcomes compared to patients. Conclusions The study highlights the critical role of dyadic coping mechanisms and self-efficacy in enhancing the QoL of patients with cervical cancer and their spousal caregivers. These findings support the need for psychosocial interventions aimed at strengthening both dyadic coping and self-efficacy to improve the overall well-being in a cancer context. The insights offer a promising avenue for nursing practice in cervical cancer, suggesting that fostering these psychosocial resources can help manage the complex demands of cancer care.